Pachamama 5 estrellas: Análisis de las estrategias publicitarias digitales de venta de suelo periurbano en Urubamba - Cusco - Vilca Gallegos, Luz Nicole (2023)
In a context of constant peri-urban transformation as a result of adaptation to new demands and expansion of urban capital in strategic investment areas, the possibility of shaping the city appears as one of the main guidelines for local development in Cusco as the city responds to systems of relationships and complementary processes of action and reaction. In this sense, within a framework of premeditated transformation, in the case of Urubamba (Cusco), an area that has seen its tourist potential increase in recent years, this work aims to analyze the advertising of two pages of lots sales as a means of crystallizing the strategies adopted by private capital to promote and generate value within those opportunity spaces. For this, we collected information from 10 advertisements of ¿A dónde vivir? and Urbania.pe carried out in 2022. It is found that there are four types of land promotion strategies, i) provision of basic services and ii) luxury services, both framed in the notion of “strategic beautification” both as complementary strategies; iii) the tourism investment model and iv) formality-legality, central components of urban transformation within spaces for sale and which are the common denominator in purchase promotion strategies. As part of the studies on peri-urbanization of agricultural land from a more subjective approach to analyze the formation of land prices, it is concluded that the generation of “competitive” rents between urban and rural lands is a central element for the demarcation of its use. Likewise, the use of these strategies are the reflection of a type of collective imagination about the area, which, in turn, contributes to the shared construction of the marketable value of the offered land.